Searching for new relevance in the 1990s: the Organization of African Unity as an instrument of conflict resolution - Dlamini, Thandeka Lungile (Rhodes University, Faculty of Humanities, Department of Political Studies, 2000)
The 1960's and the 1970's marked a great Pan-African movement in Africa, that saw the liberation of most African states. This Pan-African movement, was spearheaded by a quest to unite Africa, and to abate foreign occupation. Amidst the spirit of unity, lay a promise of an organization that would embody the hopes and aspirations of a continent undergoing a re-birth; a progression towards self-determination, economic development and integration, and the maintenance of peace. Therefore, the inception ofthe Organization of African Unity (OAD) was not only a symbol of a unifying force for Africans, but a diplomatic platform that would promote African needs on the international arena. In effect the OAU, at its inception, was for specific ideals that would guarantee liberation and unity of African states. The outcome of these ideals would be greater regional economic integration and the achievement of peace and stability. These ideals mirrored the structural definition of regional organization, with the inclusion of a Commission for Mediation Arbitration and Conciliation under the OAU Charter, to handle disputes among member states. However, the mere fact that this commission lacked the political wherewithal to resolve conflicts, by its sheer lack of a standing peacekeeping force, contributed to the inefficiency of the organization to play an effective role in conflict management. This study attempts to examine the role ofthe OAU in settling disputes. The study sought to accomplish this, in the following manner. Firstly, an investigation into the nature of conflict and why it persists in Africa was conducted. Further, an examination ofthe tools that practitioners utilize not only to study conflict, but to prevent, manage and resolve it, was done. During the investigation it was found that, although the OAU's greatest successes have come from preventive diplomacy, its structural foundations limit the capabilities of the organization to become more relevant. The Charter of the OAU alludes vaguely to the settlement of disputes, but without an executive political decision-making body able to deploy peacekeepers, its principles are largely meaningless. Amidst the growing concerns, the OAU as a matter of survival, developed initiatives it hopes will make it more effective and relevant. The focus ofthe study was the evolving role ofthe OAU, from its inception to its new role as an instrument of conflict resolution. Most of the scholarly work conducted on the OAU, is concerned with depicting a terminal organization, with little or no hope of surviving. Little emphasis is placed on prescribing remedies on how to improve and restructure the organization. The findings included, inter alia, that the organization is faced with enormous challenges, as the sources of conflict are varied and complex. Africa is now the landscape of collapsed states, economic stagnation, environmental degradation, disease and chronic conflicts. The OAU shoulders much ofthe responsibility for not sanctioning governments that contribute to the decay and suffering of the African peoples. Most ofthe criticism of the OAU, stem from the inability of the organization to play an effective role in resolving conflicts in Africa. Most of Africa's conflicts stem from a lack of political legitimacy, lack of democratic institutions, uneven distribution of resources, ethnic tensions and economic stagnation. Until such problems are addressed, Africa will continue to host the world's deadliest conflicts.
Keywords: Organization of African Unity|Africa -- Foreign relations|Conflict management -- Africa